2007
DOI: 10.1037/0096-3445.136.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype threat and working memory: Mechanisms, alleviation, and spillover.

Abstract: Stereotype threat (ST) occurs when the awareness of a negative stereotype about a social group in a particular domain produces suboptimal performance by members of that group. Although ST has been repeatedly demonstrated, far less is known about how its effects are realized. Using mathematical problem solving as a test bed, the authors demonstrate in 5 experiments that ST harms math problems that rely heavily on working memory resources-especially phonological aspects of this system. Moreover, by capitalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
387
4
12

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(436 citation statements)
references
References 70 publications
(142 reference statements)
23
387
4
12
Order By: Relevance
“…In addition, Beilock et al (2007) recently found that women under stereotype threat about their math abilities reported worrying more about and monitoring their performance. Beilock et al suggested that such thoughts contribute to the effect of stereotype threat because working memory becomes loaded with distracting information that competes for attentional resources.…”
Section: Cognitive Physiological and Affective Processes That Tax Wmentioning
confidence: 99%
“…In addition, Beilock et al (2007) recently found that women under stereotype threat about their math abilities reported worrying more about and monitoring their performance. Beilock et al suggested that such thoughts contribute to the effect of stereotype threat because working memory becomes loaded with distracting information that competes for attentional resources.…”
Section: Cognitive Physiological and Affective Processes That Tax Wmentioning
confidence: 99%
“…The current study investigates a recent assertion that stereotype threat can not only affect performance on tasks that are the target of the specific stereotype but also spill over into subsequent tasks unrelated to the stereotype (Beilock, Rydell, and McConnell, 2007). Stereotype threat refers to the fear that individuals feel of confirming negative stereotypes about a group to which they belong.…”
Section: Introductionmentioning
confidence: 99%
“…In another study that provided the impetus for the current analysis, Beilock et al (2007) tested an implication of their previous finding. In the fifth study in their series of related experiments, they presented participants with either a verbal or a spatial task after presenting the horizontal math problems under stereotype threat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations